Three Dimensional Printing and Its Applications Focusing on Microneedles for Drug Delivery - Suhair S. Al-Nimry; Rawand M. Daghmash (MDPI AG, 2023)
Microneedles (MNs) are considered to be a novel smart injection system that causes significantly low skin invasion upon puncturing, due to the micron-sized dimensions that pierce into the skin painlessly. This allows transdermal delivery of numerous therapeutic molecules, such as insulin and vaccines. The fabrication of MNs is carried out through conventional old methods such as molding, as well as through newer and more sophisticated technologies, such as three-dimensional (3D) printing, which is considered to be a superior, more accurate, and more time- and production-efficient method than conventional methods. Three-dimensional printing is becoming an innovative method that is used in education through building intricate models, as well as being employed in the synthesis of fabrics, medical devices, medical implants, and orthoses/prostheses. Moreover, it has revolutionary applications in the pharmaceutical, cosmeceutical, and medical fields. Having the capacity to design patient-tailored devices according to their dimensions, along with specified dosage forms, has allowed 3D printing to stand out in the medical field. The different techniques of 3D printing allow for the production of many types of needles with different materials, such as hollow MNs and solid MNs. This review covers the benefits and drawbacks of 3D printing, methods used in 3D printing, types of 3D-printed MNs, characterization of 3D-printed MNs, general applications of 3D printing, and transdermal delivery using 3D-printed MNs.